Improving in vitro continuous cultivation of Plasmodium cynomolgi, a model for P. vivax. (August 2022) - Christensen, Peter; Racklyeft, Annie; Ward, Kurt E.; Matheson, Jessica; Suwanarusk, Rossarin; Chua, Adeline C.Y.; Kaneko, Osamu; Aung, Htin Lin; Rénia, Laurent; Amanzougaghene, Nadia; Magneron, Victor; Lemaitre, Julien; et al.
Abstract: The absence of a routine continuous in vitro cultivation method for Plasmodium vivax, an important globally distributed parasite species causing malaria in humans, has restricted investigations to field and clinical sampling. Such a method has recently been developed for the Berok strain of P. cynomolgi, a parasite of macaques that has long been used as a model for P. vivax, as these two parasites are nearly indistinguishable biologically and are genetically closely related. The availability of the P. cynomolgi Berok in routine continuous culture provides for the first time an opportunity to conduct a plethora of functional studies. However, the initial cultivation protocol proved unsuited for investigations requiring extended cultivation times, such as reverse genetics and drug resistance. Here we have addressed some of the critical obstacles to this, and we propose a set of modifications that help overcome them.